The Natchez Indians : a history to 1735 - Barnett, James F., 1950- (University Press of Mississippi, 2007)
The Natchez Indians: A History to 1735 is the story of the Natchez Indians as revealed through accounts of Spanish, English, and French explorers, missionaries, soldiers, and colonists, and in the archaeological record. Because of their strategic location on the Mississippi River, the Nat-chez Indians played a crucial part in the European struggle for control of the Lower Mississippi Valley. The book begins with the brief con-frontation between the Her-nando de Soto expedition and the powerful Quigualtam chiefdom, presumed ances-tors of the Natchez. In the late seventeenth century Ren--and--ea.